Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.jced.5b00986
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Mutual Diffusivity of Binary Mixtures of n-Dodecane and n-Tetracontane with Carbon Monoxide, Hydrogen, and Water from Dynamic Light Scattering (DLS)

Abstract: The present work represents a continuation of a former study where the simultaneous determination of thermal and mutual diffusivity for binary mixtures of n-octacosane (n-C28H58) with dissolved carbon monoxide (CO), hydrogen (H2), or water (H2O) by using dynamic light scattering (DLS) was demonstrated. Here, the same properties are studied for binary mixtures of the n-alkanes n-dodecane (n-C12H26) or n-tetracontane (n-C40H82) with dissolved CO, H2, or H2O. In most cases, expanded relative uncertainties (k = 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 24 publications
5
55
0
Order By: Relevance
“…4(a) the synthesized FeNPs are irregular spherical and porous morphology, indicating a chain structure with a diameter ranging from 30 -100 nm. Also, they are highly prone to agglomeration, therefore the mean hydrodynamic diameters of nanoparticles were found as higher than 100 nm by DLS analysis, this state may be due to the absorption effects and particle scattering because of agglomeration [15]. Similar agglomeration behavior of nanoparticles was reported by Truskewycz et al, 2016, [2] for iron nanoparticles synthesized by using green tea extract.…”
Section: A the Characterization Of Green Synthesized Fenpssupporting
confidence: 68%
“…4(a) the synthesized FeNPs are irregular spherical and porous morphology, indicating a chain structure with a diameter ranging from 30 -100 nm. Also, they are highly prone to agglomeration, therefore the mean hydrodynamic diameters of nanoparticles were found as higher than 100 nm by DLS analysis, this state may be due to the absorption effects and particle scattering because of agglomeration [15]. Similar agglomeration behavior of nanoparticles was reported by Truskewycz et al, 2016, [2] for iron nanoparticles synthesized by using green tea extract.…”
Section: A the Characterization Of Green Synthesized Fenpssupporting
confidence: 68%
“…The limitation regarding the resolution of multiple hydrodynamic modes accessible by DLS is not only restricted to the supercritical state close to the vicinity of the plait critical point. It was also observed close to the consolute critical point of a ternary mixture [8,9], in the saturated liquid phase of a binary mixture at vapor-liquid equilibrium [10][11][12], and in the liquid state for binary mixtures near their plait critical point [13]. For the last two cases, this limitation was observed close to the region where thermal and Fick diffusivities match.…”
Section: Introductionmentioning
confidence: 71%
“…According to Figures 2(a)-2(c), it was seen that the agglomeration tendency of nanoparticles gave rise to the formation of nanoparticles which had higher mean hydrodynamic diameters. erefore, the mean hydrodynamic diameters of nanoparticles were found as higher than 100 nm by DLS analysis may be due to the absorption effects and particle scattering because of agglomeration [17]. After Cr(VI) adsorption, as shown from Figures 2(d) and 2(e), it was observed that the nanoparticles were more agglomerated, and the pores were closed due to the adsorption of Cr(VI) anions onto the adsorbent surface.…”
Section: Characterization Studiesmentioning
confidence: 90%